Prospects of culturing yeast in modified Sago effluent - Izza Zuriaty, Binti Jamari. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The study was performed to observe the potential of culturing yeast on modified sago effluent. In the process of producing starch, large volume of sago effluent is generated, directly discharged into rivers without proper treatment. Due to more intensive starch production, the volume sago effluent has increased and this can disturb the natural ecosystem. This project serves to study the potential of sago effluent for culturing yeast. In these research projects, sago effluent amendment with microbial culture (8ak-Wira MP300) as part of the effluent treatment and aerated for 3 days. This modified sago effluent was then used as medium to culture yeast. The analysis of yeast growth was done based on cell dry weight, reducing sugar and starch content. In this study, the concentration of commercial glucose was varied at 5%, 10%, 15% (w/v) were used. The growth rate of yeast was affected by this factor. 5% concentration of glucose showed the best yield of yeast. 1.04g1L or 12.01% of cell dry weight was obtained after 6 hours fermentation. 2.52g1L or 81.81 % of reducing sugar was reduced and the starch content decreased 0.41 giL or 93.18% after 24 hours fermentation. Further study should be done in order to obtain a proper nutrient of modified sago effluent